2020
DOI: 10.1101/2020.01.11.900977
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Electrophysiological Frequency Band Ratio Measures Conflate Periodic and Aperiodic Neural Activity

Abstract: Acknowledgements 32 33We would like to thank members of the Voytek Lab for insightful comments and suggestions 34 throughout this project. We would also like to express gratitude to the many people involved in 35 generating the open-access datasets and developing the open-source tools that made this project 36 possible. Abstract 39 40A common analysis measure for neuro-electrophysiological recordings is to compute the 41 power ratio between two frequency bands. Applications of band ratio measures include 42 in… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
44
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 69 publications
7
44
1
Order By: Relevance
“…The decrease of the aperiodic intercept replicates previous observations (Donoghue, Dominguez, & Voytek, 2020a;He, 2014). While on study (Donoghue et al, 2020a) investigated a correlation across the age range from 6 to 44, which is beyond the here investigated sample, the other study (He et al, 2019) found a decrease between the young and the adult group and also within the young subsample. The present analysis further indicates that this decrease is evident within the process of brain maturation during childhood and adolescence.…”
Section: Discussionsupporting
confidence: 88%
“…The decrease of the aperiodic intercept replicates previous observations (Donoghue, Dominguez, & Voytek, 2020a;He, 2014). While on study (Donoghue et al, 2020a) investigated a correlation across the age range from 6 to 44, which is beyond the here investigated sample, the other study (He et al, 2019) found a decrease between the young and the adult group and also within the young subsample. The present analysis further indicates that this decrease is evident within the process of brain maturation during childhood and adolescence.…”
Section: Discussionsupporting
confidence: 88%
“…Smaller exponents (indicating shallower PSD slopes) characterize signals with relatively strong high-frequency contributions (i.e., reduced temporal autocorrelations, and less predictability) compared to larger exponents that indicate steeper slopes. This conceptual link between PSD slopes (or high-to-low frequency power ratios that may have strong broadband slope contributions [39]) and sample entropy has been empirically observed across subjects, wakefulness and task states [14,17,40]. However, the sensitivity of fine-scale entropy to PSD slopes-a multi-scale characteristic-highlights that the contribution of slow-to-fast signal content to fine-scale entropy is unclear.…”
Section: Issue 2: Traditional Scale Definitions Lead To Diffuse Time mentioning
confidence: 90%
“…The relationship between TBR and behavioural outputs may instead be explained in differenced in the underlying aperiodic signal rather than theta and beta band specific changes 29,57 . To explore this, we extracted and analysed the aperiodic exponent from the resting and online power spectra.…”
Section: Aperiodic Signal Analysismentioning
confidence: 99%
“…Therefore, TBR may predict the effect of tRNS by improving sustained attention during tRNS. Alternatively, TBR might reflect the underlying background noise (the aperiodic signal) of the power spectrum 29 . High aperiodic exponents are thought to reflect lower excitation/inhibition ratios (E/I ratio) 30,31 .…”
Section: Introductionmentioning
confidence: 99%